Common Law, Civil Law, and Colonial Law : Essays in Comparative Legal History from the Twelfth to the Twentieth Centuries - Eves, William; Hudson, John; Ivarsen, Ingrid; White, Sarah B. (Cambridge : Cambridge University Press, 2021)
Common Law, Civil Law, and Colonial Law builds upon the legal historian F.W. Maitland's famous observation that history involves comparison, and that those who ignore every system but their own'hardly came in sight of the idea of legal history'. The extensive introduction addresses the intellectual challenges posed by comparative approaches to legal history. This is followed by twelve essays derived from papers delivered at the 24th British Legal History Conference. These essays explore patterns in legal norms, processes, and practice across an exceptionally broad chronological and geographical range. Carefully selected to provide a network of inter-connections, they contribute to our better understanding of legal history by combining depth of analysis with historical contextualization. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 02 Dec 2020).